Young driver enforcement within graduated driver licensing systems: a scoping review - Bates, Lyndel (Crime prevention and community safety, 2019)
Young drivers have the highest crash rates when compared with other groups of drivers. One countermeasure that has successfully reduced these crash rates is graduated driver licensing. However, young drivers’ compliance with graduated driver licensing requirements decreases as they gain driving experience. This paper systematically reviews the literature in order to identify how enforcement practices can be used to influence the compliance of young drivers within graduated driver licensing systems. The review identified 21 relevant studies with all bar one of these being conducted in the USA or Australia. Additionally, young drivers and parents perceive that police enforcement of young drivers within graduated driver licensing systems is inconsistent. As young drivers are more concerned about their parents finding out that they broke the road rules, there appears to be scope for greater parental involvement in this area. The use of P plates or decals for drivers on an intermediate licence may also help to facilitate police enforcement.